Analisis Strategi Pasar: Pendekatan dalam Menentukan Segmen dan Target Konsumen - Ali, Sri Indriyani; Pardalepi, Sanjes (Multidisciplinary Journal of Religion and Social Sciences, 2025)
This study aims to analyze market strategies in determining consumer segments and targets effectively in order to increase business competitiveness. The main focus of this study is to identify factors that influence market segmentation and determine marketing strategies that are in accordance with consumer needs and preferences. The research method used in this study is a qualitative descriptive approach with data collection techniques through in-depth interviews, observations, and literature studies. Data were obtained from various sources, including business actors in certain industrial sectors and market trend analysis. The analysis techniques used are SWOT analysis to understand the strengths, weaknesses, opportunities, and threats in marketing strategies, and STP (Segmenting, Targeting, Positioning) analysis to determine the right consumer segmentation and targets. The results of the study indicate that selecting specific and data-based market segments can increase the effectiveness of marketing strategies. In addition, product differentiation strategies and digital-based marketing approaches are key factors in attracting the right consumer targets. This study also found that a deep understanding of consumer behavior allows companies to develop more targeted marketing strategies that are in accordance with market preferences. Thus, this study provides insight for business actors in optimizing marketing strategies to increase competitiveness and business growth amidst increasingly competitive market competition. Keywords: Market Strategy, Consumer Segmentation, Target Market